Corporate ethics and corporate governance - Zimmerli, Walther Ch. 1945-; Holzinger, Markus; Richter, Klaus (Alfaomega, 2014)
Corporations are under fire. Hardly a day goes by that executive conduct doesn't appear as a topic - or, more accurately, as a problem - in the media. This leads to increased public pressure on corporations, many of whom are reacting and publicly assuming their corporate responsibility. This book represents an introduction to and overview of the diverse aspects of the ethical challenges confronting companies today.